Concepts and Cultural Practices of Bribri and Cabecar Ancestral Medicine in Costa Rica - García Segura, Alí (2021)
This article reflects, in the context of the COVID-19 pandemic, on the social and cultural practices of the traditional medicine of the Bribri and Cabécares native peoples of Costa Rica in dealing with contagious diseases. In order to accomplish this objective, we reviewed bibliographic sources in Anthropology, Linguistics and History, but above all, we reviewed again the interviews we had done for many years, to various the people dedicated to medicine in the indigenous Bribri and Cabecar towns. All this has allowed us to discover that many social and cultural practices, which still prevail in the Bribri and Cabecar native peoples, hide a complex system of medical concepts and protocols, which guarantee a know-how and a knowledge of how to act in the face of contagious diseases. Concepts such as quarantine, isolation, family or communal, being careful not to touch certain objects, appear with total clarity, in a conception of the world that privileges reflection on health and illness.